Studies on the genus Sinochlora Tinkham, 1945 (Orthoptera: Tettigoniidae: Phaneropterinae), I. Establishment of species groups and description of three new species - Wu, Chao; Liu, Chun-Xiang (Zootaxa, 2024)
The genus Sinochlora Tinkham, 1945 is a diverse Phaneropterinae genus in the Oriental region. Previously, the genus included 16 species, distributed in East Asia region; most species are distributed in China. After examining numerous specimens of all known species of Sinochlora, we propose that the genus Sinochlora be divided into four species groups. We also describe three new species from Pan-Himalaya and Guangxi, China: S. dulongensis sp. nov., S. makuensis sp. nov. and S. latifolia sp. nov.. A key to the species group of Sinochlora, necessary illustrations and life images of Sinochlora species are presented. The distribution of the three new species is discussed and mapped.